Epidemiological overview of HIV/AIDS in pregnant women from a state of northeastern Brazil - Claúdia Mendes da Silva; Regina de Souza Alves; Tâmyssa Simões dos Santos; Gabriela Rodrigues Bragagnollo; Clodis Maria Tavares; Amuzza Aylla Pereira dos Santos
ABSTRACT Objective: To learn the epidemiological characteristics of HIV infection in pregnant women. Method: Descriptive study with quantitative approach. The study population was composed of pregnant women with HIV/AIDS residing in the state of Alagoas. Data were organized into variables and analyzed according to the measures of dispersion parameter relevant to the arithmetic mean and standard deviation (X ± S). Results: Between 2007 and 2015, 773 cases of HIV/AIDS were recorded in pregnant women in Alagoas. The studied variables identified that most of these pregnant women were young, had low levels of education and faced socioeconomic vulnerability. Conclusion: It is necessary to include actions aimed at increasing the attention paid to women, once the assurance of full care and early diagnosis of HIV are important strategies to promote adequate treatment adherence and reduce the vertical transmission.